Racial disparity in stage at diagnosis and survival among adults with oral cancer in the US - Shiboski CH, Schmidt BL, Jordan RCK. (Blackwell Synergy, 2007)
To explore distribution of stage at diagnosis and relative survival rates among US adults with oral cavity cancer in relation to race, and over time.